2021
DOI: 10.1002/ptr.7039
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants: Treasure for antiviral drug discovery

Abstract: The pandemic of viral diseases like novel coronavirus (2019‐nCoV) prompted the scientific world to examine antiviral bioactive compounds rather than nucleic acid analogous, protease inhibitors, or other toxic synthetic molecules. The emerging viral infections significantly associated with 2019‐nCoV have challenged humanity's survival. Further, there is a constant emergence of new resistant viral strains that demand novel antiviral agents with fewer side effects and cell toxicity. Despite significant progress m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 380 publications
(387 reference statements)
0
41
0
Order By: Relevance
“…Like oleanolic acid, the other phytochemicals such as quercetin, sulfated galactomannans, 7-O-methyl-glabranine, flavonoids, glabranine, eugenol, ursolic acid, azadirachtin, D-galactose, carrageenan, chalcone 4- hydroxypanduratin A and panduratin isolated from different plants have been reported for anti-dengue virucidal activity [ 22 , 30 ]. Some already reported compounds possess anti-dengue activities are given in Table 3 [ 38 41 ]. The oleanolic acid isolated in the present study revealed the 99.17% activity against dengue-2 virus while the SFE extract revealed the 100% anti-dengue activity.…”
Section: Discussionmentioning
confidence: 99%
“…Like oleanolic acid, the other phytochemicals such as quercetin, sulfated galactomannans, 7-O-methyl-glabranine, flavonoids, glabranine, eugenol, ursolic acid, azadirachtin, D-galactose, carrageenan, chalcone 4- hydroxypanduratin A and panduratin isolated from different plants have been reported for anti-dengue virucidal activity [ 22 , 30 ]. Some already reported compounds possess anti-dengue activities are given in Table 3 [ 38 41 ]. The oleanolic acid isolated in the present study revealed the 99.17% activity against dengue-2 virus while the SFE extract revealed the 100% anti-dengue activity.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that meliacine increased host survival, and reduced by 90% the severity of clinical symptoms and the presence of viral particles in vaginal fluids. It is noteworthy that the composition of this fluid was different from the one of untreated mice, as it presented increasing amounts of IFN-gamma (2550 ± 63 pg/mL) and TNF-alpha (from 7 ± 0.9 ng/mL to 12.15 ± 0.92 ng/mL), cytokines implicated in inflammation [ 47 , 48 ]. This ability to increase cytokine production has been confirmed by another study using 56 µg/mL of meliacine applied in lipopolysaccharide-producing Escherichia coli bacterial infection [ 47 , 48 ].…”
Section: Plant-derived Antiviral Peptides (Avp) Against Dna Virusesmentioning
confidence: 99%
“…Cyclotides target HIV through interactions with the viral envelope and more specifically by disrupting the viral lipid envelope. This leads to the formation of pores, the leakage of components and the destruction of viral particles before their entry into host cells: cyclotides could prevent fusion between HIV and host cells ( Figure 1 ) [ 47 , 51 , 79 ].…”
Section: Plant-derived Antiviral Peptides Against Rna Virusesmentioning
confidence: 99%
“…The diarrhea index calculated after the resveratrol dry suspension applied to the groups of the piglets, which infected with the Rotavirus [35]. The diarrhea index formula given below of the four groups are given: Resveratrol have many antiviral properties and used against the Rotavirus diarrhea and enterovirus [39], which cause the inflammation of the hearts of mice, which reduced the hearts ability to pump he blood normally and blocked the replication of enterovirus [40]. Therefore, we use he resveratrol against the Rotavirus, which is harmful for the piglets [41], which cause diarrhea and gastroenteritis in piglets and we know that resveratrol dry suspension could regulate the immune response and inhibit the diarrhea and other viral infection [42].…”
Section: Diarrhea Indexmentioning
confidence: 99%